THE OZ BEHIND THE CURTAIN EFFECT: ETHICAL PERSPECTIVES ON THE ASSESSMENT OF SCIENTIFIC MERITS - MARIA CERNAT (Challenges of the Knowledge Society)
There is a genuine desire in Romanian research institutions to follow the rules of scientific evaluation tested over the decades in stronger academic and scientific communities such as those in the USA or the Western Europe countries. The main objective of our paper is to show that before enthusiastically embracing such rules of scientific merits evaluation a closer analysis of those norms is in order. Although the peer review system is the best method used so far, we have to analyse it and even criticize it in order to improve it. There are two points to be discussed in view of offering the right perspective on how the rules of scientific merits evaluation function: the peer-review system and the number of citations criterion. In the first part of our paper we shall investigate the shortcomings of the peer-review and the particular situations proving that the double blind review system does not always work to the benefit of scientific progress. In the second part of our study we shall examine the formalism undermining the number of citations criterion and show that we can find better alternatives. Those alternatives are not mere speculations: even prestigious institutions such as “Natural Science and Engineering Research Council of Canada” for example are giving up on the “classical” way of evaluating the scientific merits of researchers by shifting towards the content of the articles and not the number of their citations.